Juridical Analysis of Police Authority for Community Protection of Robberies that Occurred in Batam City (Research Study in the Barelang Police Legal Area) - Simanjuntak, Victor Daniel; Fadlan, Fadlan; Prasetyasari, Christiani; Fadjriani, Lia (QISTINA: Jurnal Multidisiplin Indonesia, 2023)
In writing this thesis entitled Juridical Analysis of police authority to protect the public from robbery that occurred in Batam City. One form of crime that often occurs in society is the crime of motor vehicle theft. Motor vehicle theft is a crime against property that is not uncommon in developing countries. The phenomenon of violent theft of two-wheeled motorized vehicles or what is better known as "Begal" is a type of crime that has recently become the focus of the wider community. In completing this writing and to complete the required data, the author conducted Empirical Legal research (field), by interviewing sources about the problem being researched, using qualitative data, namely sources at the Barelang Police Station in Batam City, Riau Islands regarding the Role of the Police Against Eradication of Robbery. Preventive Efforts (Prevention) Involving community leaders, youth and religious leaders to prevent acts of violence against victims of muggings Repressive Efforts (Enforcement) using various methods or tactics to reveal the perpetrators to be processed according to law. There is a role for the Barelang Police in criminal acts of theft with violence (Robbery) as regulated in Article 365 of the Criminal Code. This research shows that, in accordance with the duties and authority of the police, they carry out inquiries and investigations as well as arrest the perpetrators and process them in accordance with applicable legal provisions, as well as making efforts to prevent violent acts of theft by carrying out patrols.